"Womb for Rent": International Service Trade Employing Assisted Reproduction Technologies (ARTs). Issue 3 (14th July 2013) - Pelzman, Joseph
Abstract Infertility affects approximately 2–3 million married couples in the USA and a larger cohort of unmarried men and women. For those not inclined to adopt, science has provided another option, one based on assisted reproduction through artificial insemination, commonly known as in vitro fertilization (IVF). Under this framework a woman, designated as a "surrogate", bears a baby on behalf of the intended parents with the objective of relinquishing her rights to the child after birth. The subcontract for the services of a "surrogate" or more specifically for the use of her "womb" can be viewed as part of the literature on outsourcing of production by a vertically integrated family. The lack of universal enforcement of "surrogacy" contracts in the USA creates a demand for outsourcing of surrogacy services. One beneficiary of this uncertainty in enforcement is India which provides gestational services to intended international parents.